Thermal damage analysis of applying single- and double-slot microwave coaxial antennas for treating oblate, prolate, and circular liver tumors - Biswas, Chaity; Nasrin, Rehena; Jahan, Salma; Ferdoushi, Most. Zannatul (Journal of Naval Architecture and Marine Engineering, 2026)
Microwave coaxial antennas (MCA) are essential for effective liver tumor treatment using microwave ablation (MWA). Their configuration significantly impacts the procedure's success by ensuring precise energy delivery, efficient heating, and uniform temperature distribution. This enhances the overall efficacy and security of the medical treatment, leading to improved clinical outcomes and better patient care. In developing an MWA system, it is essential to consider the geometric characteristics of the microwave antenna construction. This research delved into the effectiveness of single- and double-slot antennas in prolate, oblate, and spherical tumor tissues. The primary goal of this investigation was to modify MWA procedures to achieve complete tumor ablation while minimizing thermal damage to adjacent healthy tissue. An MCA is inserted into liver tissue shaped like a cylinder (length 8 cm, radius 3 cm). The tissue contains a prolate ellipsoidal tumor (2.4 cm x 3.2 cm) and an oblate ellipsoidal tumor (3.2 cm x 2.4 cm). The antenna axis is selected to align with the prolate tumor's central axis and the oblate tumor's minor axis. In this simulation, we are investigating the impact of varying microwave power (6 to 24 W), frequency (600 to 3500 MHz), and time (1 to 450s) on prolate and oblate tumor cells. We are using a finite element method (FEM)-based numerical approach to assess the effectiveness of antennas. The obtained specific absorption rate (SAR) values are significantly higher when utilizing a double-slot antenna for various tumor shapes, including circular (6020.87 W/Kg), oblate (6004.54 W/Kg), and prolate (3099.50 W/Kg) tumors, in comparison to a single-slot antenna. Our findings show that with sufficient input power and frequency, necrotic tissue is mainly concentrated in the tumor, causing minimal thermal damage to the surrounding healthy tissue. Interestingly, our results indicate that double-slot antennas are less harmful to healthy tissue than single-slot antennas, even though the latter are still capable of generating high temperatures. Journal of Naval Architecture and Marine Engineering, 23(1), 2026, PP. 93-118